CARING FOR WOMEN ON THE FRONTLINES: ENHANCING WOMEN WORKERS’ CAPABILITIES AND BUILDING SOCIAL FRIENDSHIP - M.M.-Y. Yuen (Acta Theologica)
This article examines the vulnerability of frontline cleaning workers and domestic helpers during the COVID-19 pandemic and how they empower themselves by joining a community in which they can support each other. Employing surveys by non-governmental organisations, particularly those in Hong Kong, as well as my own interviews and observations, I examine the situation of the frontline workers and discuss the moral principles and conditions for upholding women’s dignity and well-being, based on the capability approach of feminist philosopher Martha Nussbaum. I argue that emphasising women’s moral agency and giving a voice to women themselves through women collectives are important in empowering them and building a life-giving community among women, especially during and after the pandemic. In addition, the notions of political charity and social friendship in Catholic social thought, particularly the social encyclical Fratelli Tutti, and the multi-axial analysis in post-colonial feminist theology are useful in upholding women’s dignity and moral agency in care situations. Examples of social friendship are provided.